Changes in Achilles tendon stiffness and energy cost following a prolonged run in trained distance runners - Fletcher, J. R.; MacIntosh, B. R. (PLOS ONE, 2018)
During prolonged running, the magnitude of Achilles tendon (AT) length change may increase, resulting in increased tendon strain energy return with each step. AT elongation might also affect the magnitude of triceps surae (TS) muscle shortening and shortening velocity, requiring greater activation and increased muscle energy cost. Therefore, we aimed to quantify the tendon strain energy return and muscle energy cost necessary to allow energy storage to occur prior to and following prolonged running. 14 trained male (n = 10) and female (n = 4) distance runners (24±4 years, 1.72±0.09 m, 61±10 kg, 64.6±5.8 ml•kg-1•min-1) ran 90 minutes (RUN) at approximately 85% of lactate threshold speed (sLT). Prior to and following RUN, AT stiffness and running energy cost (Erun) at 85% sLT were determined. AT energy return was calculated from AT stiffness, measured with dynamometry and ultrasound and estimated TS force during stance. TS energy cost was estimated on the basis of AT force and assumed crossbridge mechanics and energetics. Following RUN, AT stiffness was reduced from 328±172 N•mm-1 to 299±148 N•mm-1 (p = 0.022). Erun increased from 4.56±0.32 J•kg-1•m-1 to 4.62±0.32 J•kg-1•m-1 (p = 0.049). Estimated AT energy return was not different following RUN (p = 0.99). Estimated TS muscle energy cost increased significantly by 11.8±12.3 J•stride-1, (p = 0.0034), accounting for much of the post-RUN increase in Erun (8.6±14.5 J•stride-1,r2 = 0.31). These results demonstrate that a prolonged, submaximal run can reduce AT stiffness and increase Erun in trained runners, and that the elevated TS energy cost contributes substantially to the elevated Erun.